CFD Approach towards Natural Ventilation Design: Guidelines for Houses in Thailand - Tantasavasdi, Chalermwat (Journal of Architectural/Planning Research and Studies (JARS), 2002)
This paper explores the potential of using natural ventilation as a passive cooling system for house designs in Thailand by using computational fluid dynamics (CFD). The characteristics of past and present Thai houses are analyzed in terms of climate, culture, and technology. Based on the thermal comfort requirements for the Thai people and the climate conditions in Bangkok, the study has found that it is possible to use natural ventilation to create a thermally comfortable indoor environment in houses in a Bangkok suburb during 20% of the year. The analysis of site planning reveals that houses with compact shape have a better ventilation rate than those with elongated shape. To maximize the ventilation rate, the study of a prototype house finds that the size of the openings has to exceed 40% of the area of the house. This research also develops comprehensive design guidelines for natural ventilation at both the site planning and individual house levels.